2016
DOI: 10.1111/jgh.13240
|View full text |Cite
|
Sign up to set email alerts
|

Additive impact of pre‐liver transplant metabolic factors on survival post‐liver transplant

Abstract: Concomitant diabetes and obesity but not each condition in the absence of the other is associated with reduced post-liver transplant survival. The impact of diabetes and obesity is greater in older patients and those with hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…Currently, NASH-related cirrhosis is frequently missed as a diagnosis with the consequence of presenting with more advanced liver disease and HCC, thereby limiting potential curative options including transplantation. (30) In addition, with the increasing prevalence of metabolic factors (diabetes, overweight, or obesity), which have a negative impact on wait-list dropout rates (31) and survival after LT, (32) strategies to optimize weight and diabetes control and avoid sarcopenia should be prioritized in these patients within LT programs.…”
Section: Original Article | 33mentioning
confidence: 99%
“…Currently, NASH-related cirrhosis is frequently missed as a diagnosis with the consequence of presenting with more advanced liver disease and HCC, thereby limiting potential curative options including transplantation. (30) In addition, with the increasing prevalence of metabolic factors (diabetes, overweight, or obesity), which have a negative impact on wait-list dropout rates (31) and survival after LT, (32) strategies to optimize weight and diabetes control and avoid sarcopenia should be prioritized in these patients within LT programs.…”
Section: Original Article | 33mentioning
confidence: 99%
“…[4][5][6] This might be due to the fact that OB patients have concomitant predisposing factors for HCC such as the presence of nonalcoholic fatty liver disease (NAFLD) or chronic and systemic inflammatory status caused by excessive adipose tissue. 7,8 Studies on obese patients undergoing liver transplantation (LT) for HCC have also shown inferior survival when compared to normal weight patients ( [9][10][11] or patients with higher ratio between visceral fat and muscular mass (12). However, these studies are from single centers and less generalizable.…”
Section: Introductionmentioning
confidence: 99%
“…Seminal findings in the following fields have been published as a result of these collaborations: posttransplant prevention of hepatitis B recurrence after transplant, outcomes of LT in HCC patients selected according the UCSF criteria, outcomes of LT in patients transplanted for hepatitis C–related cirrhosis, prevention of bone disease after LT, outcomes for patients with hemochromatosis, outcomes for patients of Aboriginal or Torres Straight ethnicity, rates of colorectal malignancy, and longterm outcomes for liver transplant patients surviving beyond 12 months . More recently the effect of pretransplant metabolic factors on longer‐term outcomes have been described for liver transplant recipients in Australia and New Zealand …”
Section: Discussionmentioning
confidence: 99%
“…(16) More recently the effect of pretransplant metabolic factors on longer-term outcomes have been described for liver transplant recipients in Australia and New Zealand. (17) FIG. 5.…”
Section: Australian and New Zealand Liver Transplant Clinical Researcmentioning
confidence: 99%